The linear and non-linear optical absorption and asymmetrical electromagnetic interaction in chiral twisted bilayer graphene with hybrid edges. (August 2020) - Mu, X.; Sun, M.
Abstract: In this work, we theoretically study the linear and non-linear optical absorption properties of graphene, armchair, zigzag, and hybrid edge bilayer graphene (BLG) and visualize the exciton localization and charge transfer behavior of its transition process. Then, the relationship between the Moiré pattern and the chiral properties of BLG is revealed by the visualization method. We found that the energy level of the Moiré pattern is between the orbital energy levels of the zigzag and the armchair edges, and the addition of Moiré can significantly enhance the interlayer charge transfer of normal BLG and twisted BLG. Moiré itself has a local effect on charge transfer excitons and local excitons on BLG. Moreover, the Moiré can effectively regulate the distribution of the magnetic transition dipole moment to control the chirality of twisted bilayer graphene (TwBLG). These laws will help the application of TwBLG in optical and optoelectronic devices. These regulars will guide the design and manufacture of TwBLG-based optoelectronic, photobiological, and photochemical reaction devices. Graphical abstract: Image 1 Highlights: We report the linear and non-linear optical absorption properties of graphene, armchair, zigzag, and hybrid edge bilayer and visualize the local and charge transfer behavior of its transition process. The chiral properties of bilayer graphene (BLG) were visualized. The Moiré energy level is between the orbital energy levels of the zigzag edge and the armchair edge, and the addition of Moiré can significantly enhance the interlayer charge transfer of normal BLG and reverse BLG. Moiré itself has a local effect on charge transfer excitons and local excitons on BLG. Moreover, the moiré can effectively regulate the distribution of the magnetic transition dipole moment to control the chirality of twisted bilayer graphene (TwBLG). These laws will help the application of TwBLG in optical and optoelectronic devices. Our results can guide the design and manufacture of TwBLG-based optoelectronic, photobiological, and photochemical reaction devices.